Isolation and identification of Fungi from the Animal Dung in Thamar-Yemen and Estimation of the Antagonistic Activity of Papulospora sp. against Fusarium oxysporum - moghalles, mahmoud; albader, salah (Yemeni Journal of Agriculture & Veterinary Sciences, 2021)
This study was conducted in Thamar province – Yemen, and aimed to isolation and identification of fungi from the animal dung and testing the antagonism activity between the Papulaspora sp. isolated from the animal dung against Fusarium oxysporum. Twenty five dung samples of cows(12) and sheep(13) were collected from three different locations of Thamar province/ Yemen.By the moist chamber method, fifteen fungi were isolated (6 Hyphmycetes,5 Ascomycetes, 3 Zygomycetes,and 1Basidiomycetes); they include Absidia corymbifera, Ascodesmis spherospora, Aspergillusflavus, A.niulans, Caetomium globusum, C.spirale, Coprinus sp., Kernia nitida, Mucor circinelloidis, Papulaspora sp., Phoma herbarum, Pithomyces sp., Rhizopus stolonifera, Sporormiella minima..The species richness of samples was different according to the samples location, as well as to the type of samples. Papulaspora sp. was selected as antagonist against Fusarium oxysporum ,the results revealed that the growth in the medium of the potato dextrose agar showed a high effect of Papulaspora isolate on the radial growth of pathogenic isolate of F. oxysporum .At the same time, Papulaspora sp did not affect on neither the seeds germination% nor on seedlings growth of tomato. It is worthy to mention that the recent study was regarded as a new investigation about antagonism efficacy of Papulaspora.